2009
DOI: 10.4049/jimmunol.0801882
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role for STAT3 in IL-17A-Mediated CCL11 Expression in Human Airway Smooth Muscle Cells

Abstract: IL-17A has been shown to be expressed at higher levels in respiratory secretions from asthmatics and to correlate with airway hyperresponsiveness. Although these studies raise the possibility that IL-17A may influence allergic disease, the mechanism remains unknown. We previously demonstrated that IL-17A mediates CC chemokine (CCL11) production from human airway smooth muscle (ASM) cells. In this study, we demonstrate that STAT3 activation is critical in IL-17A-mediated CCL11 expression in ASM cells. IL-17A me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 49 publications
6
55
1
Order By: Relevance
“…Because Stat3 could be phosphorylated by activated ERK1/2, JNK, or p38 (at Ser 727 ), we further investigated which MAPK pathway may be involved. We observed that ERK1/2, p38, and JNK exhibit time-dependent phosphorylation in HSCs upon IL-17A restimulation, and their response to rmIL-17A restimulation is rapid (within 30 min), like previously observed in human airway smooth muscle cells (45,46). Furthermore, pharmacological inhibition of ERK1/2 or p38 decreased collagen and a-SMA expression in rmIL-17A-challenged or quiescent HSCs.…”
Section: Discussionsupporting
confidence: 61%
“…Because Stat3 could be phosphorylated by activated ERK1/2, JNK, or p38 (at Ser 727 ), we further investigated which MAPK pathway may be involved. We observed that ERK1/2, p38, and JNK exhibit time-dependent phosphorylation in HSCs upon IL-17A restimulation, and their response to rmIL-17A restimulation is rapid (within 30 min), like previously observed in human airway smooth muscle cells (45,46). Furthermore, pharmacological inhibition of ERK1/2 or p38 decreased collagen and a-SMA expression in rmIL-17A-challenged or quiescent HSCs.…”
Section: Discussionsupporting
confidence: 61%
“…Written informed consent for airway smooth muscle (ASM) harvesting was obtained from all patients. HASM cells were cultured and maintained as described earlier (22)(23)(24)(25)(26).…”
Section: Isolation and Culture Of Hasm Cellsmentioning
confidence: 99%
“…STAT3 has recently been implicated to play a critical role in promoting allergic inflammation, notably in studies where epithelial STAT3 disruption reduced the airway eosinophilia (21), and IL-17A-induced STAT3 activation mediated the eotaxin-1/CCL11 induction in HASM (22). However, despite the increased interest in pathophysiology of TSLP in inflammatory diseases such as asthma (6), cellular targets and TSLPR-associated cell signaling mechanisms and functions remain poorly understood.…”
mentioning
confidence: 99%
“…50 Interestingly, a recent report showed that Stat3 is critical for IL-17-mediated CCL11 expression in human airway smooth muscle cells. 51 However, more direct evidence for the roles of JAK/PI3K and JAK/Stat in IL-17 signaling are needed to avoid secondary effects because JAKs can be strongly activated by IL-17-induced cytokines, such as IL-6. mRNA stability.…”
Section: Il-17 Signalingmentioning
confidence: 99%